2016
DOI: 10.1038/ncomms10147
|View full text |Cite
|
Sign up to set email alerts
|

Local admixture of amplified and diversified secreted pathogenesis determinants shapes mosaic Toxoplasma gondii genomes

Abstract: Toxoplasma gondii is among the most prevalent parasites worldwide, infecting many wild and domestic animals and causing zoonotic infections in humans. T. gondii differs substantially in its broad distribution from closely related parasites that typically have narrow, specialized host ranges. To elucidate the genetic basis for these differences, we compared the genomes of 62 globally distributed T. gondii isolates to several closely related coccidian parasites. Our findings reveal that tandem amplification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
321
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 232 publications
(338 citation statements)
references
References 67 publications
15
321
1
1
Order By: Relevance
“…Phylogenetic network of major T. gondii strain types based on genome-wide single nucleotide polymorphisms (72). The major strain types are denoted by reference strains (haplotypes in parentheses) that are clustered by clades.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic network of major T. gondii strain types based on genome-wide single nucleotide polymorphisms (72). The major strain types are denoted by reference strains (haplotypes in parentheses) that are clustered by clades.…”
Section: Figurementioning
confidence: 99%
“…Sampling from Africa is somewhat sporadic, but at least one haplotype commonly found in Africa (i.e., type 14) is related to type 6 strains found in both Europe and South America, suggesting a global distribution for this clade (78). Recent studies based on whole-genome sequencing of more than 60 strains of T. gondii revealed that the population structure is shaped by recent admixture resulting in coinheritance of large chromosomal haploblocks that are conserved between members of a common clade (72). Moreover, these conserved haploblocks are enriched in secreted pathogenicity determinants that interact with the host (72), as discussed further below.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…gondii has a complex life cycle, and the parasite's ability to differentiate through its life stages in response to stresses and environmental conditions is fundamental for its pathogenicity and transmission (3). Transcriptome analyses have revealed that a large percentage of mRNAs show life stage-specific expression (4) and/or cell cycle regulation (5).…”
mentioning
confidence: 99%
“…ponents in order to create an environment in which they can survive (64)(65)(66)(67)(68). Without this ability, the host cell's innate defense mechanisms could overcome the parasite and prevent its reproduction or egress (69).…”
Section: Compounds With Proposed Modes Of Actionmentioning
confidence: 99%